Greenhouse gas emissions during storage of manure and digestates: Key role of methane for prediction and mitigation. (October 2018) - Baral, Khagendra R.; Jégo, Guillaume; Amon, Barbara; Bol, Roland; Chantigny, Martin H.; Olesen, Jørgen E.; Petersen, Søren O.
Abstract: Treatment of liquid manure and other wastes by anaerobic digestion (AD) adds to renewable energy targets, and it is thus a favorable strategy for greenhouse gas (GHG) mitigation. Both untreated manure and digestates are typically stored for a period in order to recycle nutrients for crop production, and emissions of methane (CH4 ), nitrous oxide (N2 O) and ammonia (NH3 ) during storage contribute to the overall GHG balance. We determined emissions of all three gases during summer and autumn storage of digestates and untreated manure in pilot-scale experiments. Using these and other data, GHG balances were calculated for treatment, post-treatment storage, and field application. The GHG mitigation potential of AD was demonstrated, but CH4 emissions during storage dominated the overall GHG balance irrespective of treatment; hence for GHG inventories and mitigation efforts, the correct estimation of this source is critical. Current inventory guidelines from the Intergovernmental Panel on Climate Change (IPCC) estimate CH4 emissions from manure management based on a simple classification of livestock production systems, volatile solids (VS) excreted, and annual average temperature, and the effects of treatment and management at farm level are therefore not accounted for in any detail. Two empirical models were evaluated, which instead calculate VS degradation and storage temperature with daily time steps; both models were based on concepts presented by Sommer et al. (2004) . Parameters for the Arrhenius temperature relationship of CH4 production, i.e., apparent activation energy, E a, and pre-exponential factor, A, could be selected, for which cumulative CH4 emissions calculated with the two models approached observed emissions. However, the magnitude of emissions during a warm period was not well reproduced, and the parameters identified for the two models differed. Sensitivity analyses showed that deviations from observations could not be explained by errors in manure storage temperature. The results thus suggest that CH4 emissions cannot be predicted from VS and temperature alone, i.e., that the methanogenic potential changes during storage. Determination of parameters for estimation of CH4 emissions from manure management is discussed with reference to recent literature. Highlights: Greenhouse gas (GHG) emissions were determined during storage of digestates and manure. In GHG balances for treatment, storage and field, methane emission during storage always dominated Two empirical models were parameterised in order to predict daily methane emissions. Temperature functions differed, but neither model described emissions during a warm period. Temperature response parameters should account for variations in methanogenic potential.